A comparison of human natural monoclonal antibodies and aptamer conjugates for promotion of CNS remyelination: where are we now and what comes next?. (4th May 2018) - Perwein, Maria K.; Smestad, John A.; Warrington, Arthur E.; Heider, Robin M.; Kaczor, Mark W.; Maher, Louis J.; Wootla, Bharath; Kunbaz, Ahmad; Rodriguez, Moses
ABSTRACT: Introduction : Multiple sclerosis (MS) is a chronic and progressive inflammatory demyelinating disease of the human central nervous system (CNS) and is the most common disabling neurological condition in young adults, resulting in severe neurological defects. No curative or long-term progression-inhibiting therapy has yet been developed. However, recent investigation has revealed potential strategies that do not merely modulate potentially pathogenic autoimmune responses, but stimulate remyelination within CNS lesions. Areas covered : We discuss the history and development of natural human IgM-isotype immunoglobulins (HIgMs) and recently-identified aptamer-conjugates that have been shown to enhance endogenous myelin repair in animal models of demyelination by acting on myelin-producing oligodendrocytes (OLs) or oligodendrocyte progenitor cells (OPCs) within CNS lesions. We also discuss future development aims and applications for these important novel technologies. Expert opinion : Aptamer conjugate Myaptavin-3064 and recombinant human IgM-isotype antibody rHIgM22 regenerate CNS myelin, thereby reducing axonal degeneration and offering the potential of recovery from MS relapses, reversal of disability and prevention of disease progression. Advancement of these technologies into the clinic for MS treatment is therefore a top priority. It remains unclear to what extent the therapeutic modalities of remyelinating antibodies and aptamers may synergize with other currently-approved therapies to yield enhanced therapeutic effects.